The Development and Analysis of a Preliminary Electrodialysis Process for the Purification of Complex Lithium Solutions for the Production of Li2CO3 and LiOH - Alonso González; Geovanna Choque; Mario Grágeda; Svetlana Ushak (Membranes, 2025)
Direct lithium extraction (DLE) is emerging as a promising alternative to brine extraction although it requires further processing to obtain high-quality products suitable for various applications. This study focused on developing a process to concentrate and purify complex LiCl solutions obtained through direct lithium extraction (DLE). Two different chemical compositions of complex LiCl solutions were used, dividing the study into three stages. In the first part, lithium was concentrated to 1% by mass by evaporation. In the second, electrodialysis was used to alkalinize the LiCl solution and remove magnesium and calcium impurities under different current densities. The best results obtained were magnesium and calcium removals of 99.8% and 98.0%, respectively, and lithium recoveries of 99% and 96%. In the third stage, the selectivity of two different commercial cationic membranes (Nafion 117 and Neosepta CMS) was evaluated to separate Li+, K+, and Na+ cations under different current densities and volumetric flow rates. The Neosepta CMS membrane demonstrated higher lithium recovery. This study evaluated the quality of the purified lithium-rich solution and its potential use both in the production of Li2CO3 as well as in the electrochemical production of LiOH.